2018
DOI: 10.1111/mec.14501
|View full text |Cite
|
Sign up to set email alerts
|

Gene expression profiling across ontogenetic stages in the wood white (Leptidea sinapis) reveals pathways linked to butterfly diapause regulation

Abstract: In temperate latitudes, many insects enter diapause (dormancy) during the cold season, a period during which developmental processes come to a standstill. The wood white (Leptidea sinapis) is a butterfly species distributed across western Eurasia that shows photoperiod-induced diapause with variation in critical day-length across populations at different latitudes. We assembled transcriptomes and estimated gene expression levels at different developmental stages in experimentally induced directly developing an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 97 publications
1
24
0
Order By: Relevance
“…Gene expression levels were assessed using recently published RNA-seq data obtained for distinct developmental stages of L. sinapis (Leal et al. 2018).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Gene expression levels were assessed using recently published RNA-seq data obtained for distinct developmental stages of L. sinapis (Leal et al. 2018).…”
Section: Methodsmentioning
confidence: 99%
“…Substantial changes in overall gene expression between developmental stage transitions has previously been observed (e.g., Leal et al. 2018), but the impact of metamorphosis on temporal patterns of dosage compensation has not been thoroughly analyzed in any lepidopteran species.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of sequence databases is very useful for a better understanding of host-pathogen interactions 19 , feeding mechanisms 20 , development 21 , and defense pathways in phytophagous insects 22 . Additionally, a significant number of studies using transcriptomic-based approaches have focused on identifying genes involved in developmental processes, with expression profiles among different life stages reported in several insect species 21,23,24 . Recent studies have reported such gene expression analyses across different developmental stages in lepidopteran pests of global economic relevance 2426 .…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, we show that environmental conditions (we predict cold temperature in this case) modulate the timer and propose that this may occur through cryoprotectant accumulation. Accumulation of small molecule cryoprotectants (e.g., sorbitol, alanine, etc) in response to cold exposure has been observed in diapause and implicated in diapause termination in other insects (e.g., Leal et al, ; Lehmann et al, ; Michaud & Denlinger, ; Wang, Egi, Takeda, Oishi, & Sakamoto, ). Calcium signalling mediates osmotic stress due to small molecule cryoprotectant accumulation in insects (Storey, ).…”
Section: Discussionmentioning
confidence: 99%
“…Accumulation of small molecule cryoprotectants (e.g., sorbitol, alanine, etc) in response to cold exposure has been observed in diapause and implicated in diapause termination in other insects (e.g., Leal et al, 2018;Lehmann et al, 2018;Michaud & Denlinger, 2007;Wang, Egi, Takeda, Oishi, & Sakamoto, 2014). Calcium signalling mediates osmotic stress due to small molecule cryoprotectant accumulation in insects (Storey, 1990).…”
Section: Diapause Termination As a Model Of Long-term Timekeepingmentioning
confidence: 99%